CSR Image and Customer Satisfaction: The Mediating Role of Customer Trust and Customer Loyalty - Saira Irfan (CSRC Publishing, 2021)
Purpose: This study aims to examine the impact of Corporate Social Responsibility (CSR) image on customer satisfaction in the context of the banking sector of Pakistan. Further, the intervening role of customer trust and customer loyalty in the relationship between CSR image and customer satisfaction is also examined.